An initial overview of tidal and sea level variability in Cyprus - Nikolaidis, Marios; Danezis, Chris (My University, 2020)
Tide gauges remain the fundamental instrument used to measure water level in the coastal environment. Issues surrounding the calibration and vertical datum control of tide gauges are therefore fundamental in studies involving the determination of absolute sea level and its variation over time. In this article, we collected and analyzed data from five tide gauge stations, located in strategic positions around the Cyprus island. During the analysis the following tidal datums were determined: Mean Sea Level (MSL), Mean Tide Level (MTL), Mean High Water (MHW), Mean Higher High Water (MHHW), Mean Low Water (MLW) and Mean Lower Low Water (MLLW). These were calculated temporarily using the available data observed since December 2019. Using the Doodson X0 filter for suppressing the effect of the astronomical tide on the MSL, this preliminary methodology provides some insight regarding the Absolute Mean Sea Level and Mean Tide Level of Cyprus.
Keywords: Cyprus; Sea Level; Tidal Datum; Tide Gauge; Tides